1977
DOI: 10.1111/j.1432-1033.1977.tb11726.x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Assembly in vitro. Purification of Assembly-Promoting Factors

Abstract: The role of microtubule-associated proteins in the assembly of tubulin to microtubules in vitro has been studied.1. It has been confirmed that pure tubulin obtained by phosphocellulose column chromatography does not significantly assemble in vitro in the absence of minor components which co-polymerize with tubulin. Although tubulin aggregates in a morpholino-ethanesulfonate buffer containing high Mg2 + concentrations, this process was neither inhibited by Ca2+ or colchicine, nor reversed by cold exposure.2. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(156 citation statements)
references
References 21 publications
4
151
1
Order By: Relevance
“…We also found that tau decreases the rate and extent of microtubule growth in cells. These data are in contrast to the widely recognized ability of tau to promote microtubule growth and assembly under non-steady state conditions, both in vitro (Cleveland et al, 1977;Fellous et al, 1977) and in cells (Caceres and Kosik, 1990;Knops et al, 1991;Esmaeli-Azad et al, 1994; reviewed in Buee et al, 2000). They are also in contrast to the taumediated enhancement of the rate and extent of microtubule growth observed in dynamics studies in vitro, also under non-steady state conditions of net microtubule assembly (Drechsel et al, 1992;Trinczek et al, 1995).…”
Section: Tau Suppresses Microtubule Dynamics In Cellsmentioning
confidence: 62%
“…We also found that tau decreases the rate and extent of microtubule growth in cells. These data are in contrast to the widely recognized ability of tau to promote microtubule growth and assembly under non-steady state conditions, both in vitro (Cleveland et al, 1977;Fellous et al, 1977) and in cells (Caceres and Kosik, 1990;Knops et al, 1991;Esmaeli-Azad et al, 1994; reviewed in Buee et al, 2000). They are also in contrast to the taumediated enhancement of the rate and extent of microtubule growth observed in dynamics studies in vitro, also under non-steady state conditions of net microtubule assembly (Drechsel et al, 1992;Trinczek et al, 1995).…”
Section: Tau Suppresses Microtubule Dynamics In Cellsmentioning
confidence: 62%
“…After a final centrifugation step at 4 "C (100000 x g, 30 min), to remove some aggregated protein, the microtubule protein solution in buffer A was made 0.75 M in NaCl and 10 mM in 2-mercaptoethanol [21]. The final protein concentration was approximately 8 mg/ml.…”
Section: Fractionation Of Microtubule-associated Proteinsmentioning
confidence: 99%
“…We isolated heat-stable associated proteins from total microtubule protein in a manner similar to that used by Nunez and coworkers [21]. Microtubule protein, purified by three temperaturedependent cycles of polymerization/depolymerization in buffer A, was incubated for 4 min at 98 "C in the presence of 0.75 M NaCl and 10 mM 2-mercaptoethanol (see Materials and Methods).…”
Section: Fractionation Of Microtubule-associated Proteinsmentioning
confidence: 99%
“…While tau factor is essential for the tubulin to assemble [2][3][4][5][6], Ca 2+-dependent association of calmodulin with tau factor prevents the tan from interacting with tubulin thus inhibiting or reversing tubulin assembly. At decreased Ca2+levels, calmodulin-tau interaction ceases, leading to the interaction of tau-tubulin, with the consequent assemby-formation.…”
Section: Discussionmentioning
confidence: 99%
“…When the tubulin is freed of the microtubule-associated proteins by phosphocellulose chromatography, it can no longer assemble into the microtubules under standard polymerization conditions. Addition of the tau proteins back to the PC-tubulin fully restored its polymerizability [2][3][4][5][6]. In [3] it was concluded that tau is both necessary and sufficient for nucleation and elongation of microtubules from PC-tubulin.…”
mentioning
confidence: 99%